LEVEL OF COMMUNITY PARTICIPATION IN BIRTH CERTIFICATE OWNERSHIP IN PERAK EAST DISTRICT, PABEAN CANTIAN DISTRICT, SURABAYA CITY - Dewantara, Ervin (Universitas 17 Agustus 1945 Surabaya, 2024)
A birth certificate is evidence or a sign that clarifies the child who was born, usually the legal status begins when the human is born from life to death. A birth certificate is strong evidence of the existence of a child because the birth certificate clearly states the day of birth, place of residence, date of birth, month of birth, and year of birth and it clearly states the names of the parents who gave birth. Therefore, this study discusses the level of community participation in the ownership of birth certificates. This study aims to measure the level of participation of the silver east community in the ownership of birth certificates. The type of research used in this research is descriptive quantitative. Descriptive quantitative research method is a method that aims to make a picture or descriptive about a situation objectively using numbers, starting from data collection, interpretation of the data as well as appearance and results. The data collection technique uses the questionnaire method, namely by giving a set or written questions or questions to respondents to be answered. Based on the results of research that has been carried out on the Level of Community Participation in Birth Certificate Ownership in Perak Timur Village, Pabean Cantian District, Surabaya City, the conclusions are: from the theory proposed by Keith Davis which has three indicators, namely individual mental and emotional involvement, individual motivation and individual responsibility, the highest value of the 3 indicators of community participation is 88%.